MELUKIS GRAFIK FUNGSI YANG RUMIT DENGAN MUDAH - Faiz Ahyaningsih (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2013)
This paper aim how to sketch the complicated curve y = f(x) easily. Before it we must know about the domain, range, discontinuity, symmetry, intercepts, extent, critical points, concavity, and asymptotes. The behavior of curve over the x where no f’(x) is observed, also odd function and even function. That’s many aspect of sketching curve.